1992
DOI: 10.1029/92ja00433
|View full text |Cite
|
Sign up to set email alerts
|

Periodic magnetopause oscillations observed with the GOES satellites on March 24, 1991

Abstract: The GOES 6 and 7 satellites were in the dayside magnetosphere late on March 24, 1991, when the magnetopause moved in to geosynchronous orbit. Observations on GOES 6 near 1030 local time (LT) indicated six inward and outward periodic movements of the magnetopause past the satellite over a 30-rain interval. Later the magnetopause moved farther in, placing GOES 6 (1100 LT) in the magnetosheath and then moving in past GOES 7, near 1245 LT. The periodic oscillations of the magnetopause at GOES 6 suggest surface wav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 23 publications
(25 reference statements)
2
28
0
1
Order By: Relevance
“…However, statistical studies by ground‐based magnetometers of Pc‐5 waves indicate that the preponderance of ULF wave activity occurs on the flanks, with perhaps more activity in the dawn sector [ Anderson et al , 1990; Ruohoniemi et al , 1991]. Further, if the ULF wave activity is a result of flow instabilities along the flanks [ Cahill and Winckler , 1992; Mann et al , 1999; Mathie and Mann , 2000b], one would expect the wave power to be directed generally tailward, i.e., propagating eastward in the dusk sector and westward in the dawn sector. How would electron acceleration be affected in each case?…”
Section: Local Time and Propagation Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, statistical studies by ground‐based magnetometers of Pc‐5 waves indicate that the preponderance of ULF wave activity occurs on the flanks, with perhaps more activity in the dawn sector [ Anderson et al , 1990; Ruohoniemi et al , 1991]. Further, if the ULF wave activity is a result of flow instabilities along the flanks [ Cahill and Winckler , 1992; Mann et al , 1999; Mathie and Mann , 2000b], one would expect the wave power to be directed generally tailward, i.e., propagating eastward in the dusk sector and westward in the dawn sector. How would electron acceleration be affected in each case?…”
Section: Local Time and Propagation Effectsmentioning
confidence: 99%
“…Ground observations suggest that Pc‐5 ULF oscillations are most prevalent in the dawn sector of the magnetosphere [ Anderson et al , 1990; Ruohoniemi et al , 1991; Glassmeier and Stellmacher , 2000], and have a higher occurrence rate during periods of high solar wind speed [ Kokubun et al , 1989; Engebretson et al , 1998]. The source of wave power driving Pc‐5 oscillations has been speculated to be either through Kelvin‐Helmholtz waves generated by the flow of the solar wind past the magnetospheric boundary surface [ Cahill and Winckler , 1992; Mann et al , 1999], or through variations in the solar wind pressure propagating as wave energy into the magnetosphere [ Lysak and Lee , 1992]. In a study examining phase velocities of magnetospheric ULF waves, Mathie and Mann [2000b] found that morning‐sector waves during high speed solar wind events ( v sw ≃ 500 km/s) were likely driven by magnetopause flow instabilities, whereas during lower solar wind velocities observed ULF pulsations were likely a result of the impulsive action of the solar wind.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, it has been shown for example that solar wind speed (V sw ) correlates with ULF power in the Pc3 to Pc5 frequency range (1.7 to 100 mHz) [e.g., Greenstadt et al, 1979;Mathie and Mann, 2000;Pahud et al, 2009;Simms et al, 2010;Rae et al, 2012], with a likely physical mechanism being the generation of shear flow instabilities along the magnetopause [Cahill and Winckler, 1992;Mann et al, 1999;Mathie and Mann, 2000]. Solar wind dynamic pressure changes (P dyn ) have also been found to be correlated with ULF wave excitation [e.g., Kepko et al, 2002;Takahashi and Ukhorskiy, 2007;Kessel, 2008], possibly due to the generation of compressional waves that transmit their energy to field line resonances in the inner magnetosphere [Kivelson and Southwood, 1988;Lysak and Lee, 1992;Mann et al, 1995;Hartinger et al, 2011].…”
Section: Introductionmentioning
confidence: 99%
“…To date, several studies on the event of 24 March 1991 have been reported in the literature (Cahill and Winckler 1992;Yumoto et al 1992;Fujitani et al 1993;Liu et al 1993;Reddy et al 1994;Trivedi et al 1997;Schott et al 1998). Most of these studies focused on a local investigation of the characteristics and driving causes of the pulsations through an analysis of the data obtained solely from ground stations or from satellites.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these ULF waves are categorized as the Pc 5 waves (1.7 < f < 6.7 mHz). The ground-based and satellite observations of the Pc 5 waves have been reported for a few decades (e.g., Brown et al 1968;Barfield and McPherron 1972;Takahashi et al 1986Takahashi et al , 1987Takahashi et al , 1990Cahill and Winckler 1992;Kepko et al 2002;Kepko and Spence 2003). Generally speaking, according to their dominant variations, these waves are categorized as compressional and transverse Pc 5 waves.…”
Section: Introductionmentioning
confidence: 99%